A systematic approach for analysis, interpretation, and reporting of coronary CTA studies - Karlo, Christoph A. (Springer-Verlag, 2012)
Over the past years, the number of coronary computed tomography angiography (CTA) studies performed worldwide has been steadily increasing. Performing a coronary CTA study with appropriate protocols tailored to the individual patient and clinical question is mandatory to obtain an image quality that is diagnostic for the study purpose. This process can be considered the primary mainstay of each coronary CTA study. The secondary mainstay is represented by the correct analysis and interpretation of the acquired data, as well as reporting of the pertinent imaging findings to the referring physician. The latter process requires knowledge of the advantages and disadvantages of various post-processing methods. In addition, a standardized approach can be helpful to avoid false-positive and false-negative findings regarding the presence or absence of coronary artery disease. By implementing various radiation dose reduction techniques, care needs to be taken to keep the radiation dose of coronary CTA as low as reasonably achievable while maintaining the diagnostic capacity of the examination. This review describes a practical approach to the analysis and interpretation of coronary CTA data, including the standardized reporting of the relevant imaging findings to the referring physicians.